Reliability and construct validation of the Filipino version of the modified checklist for autism in toddlers (M-CHAT FV) - Tanchanco, Lourdes Bernadette S.
Background: Autism is a complex neurodevelopmental disorder that presents with impairments in social communication and repetitive behavior. Early detection and intervention improves outcomes of children. No autism-specific screening tool has been validated in the Philippines.